Transformation of Progressive Islamic Education - Muhammad Muchlasul Amal; Wantini (al-Afkar, Journal For Islamic Studies, 2025)
Islamic education in Indonesia has undergone a significant transformation from the tradition of Islamic boarding schools that focus on religious values to the concept of progressive Islamic education that combines tradition and modernity. This research aims to examine the relevance of progressive Islamic education in answering the challenges of globalization with a focus on the integration of spiritual, intellectual, and technological values. The research method used is a literature study with a descriptive-analytical approach to the works of Fazlur Rahman, Haedar Nashir, and other figures. The results of the study show that progressive Islamic education aims to create a critical, ethical, and innovative generation through a curriculum that integrates Islamic values and modern science. The concepts of humanization, liberation, and transcendence are the main cornerstones of this education, with an orientation on character development and global competence. Technology integration, curriculum reform, and inclusivity are the keys to the sustainability of Islamic education in facing the challenges of the digital era and the 21st century.